Economic Analysis of Floricultural Plants Production in Kwara State, North Central Nigeria - A, Muhammad-Lawal; A. H, Adenuga; K. B, Olatinwo; T. A, Saadu (Asian Journal of Agriculture and Rural Development, 2012)
In spite of the substantial contribution of floriculture to the Nigerian economy, there is still a low level of awareness on the potential of the horticultural subsector of the Nigerian agricultural sector to generate employment and reduce poverty. This study therefore carried out an assessment of the economics of floricultural plants production in Kwara State, Nigeria. The study specifically estimated the returns to farmer’s labour and management. It also assessed the determinants of returns to floricultural plant production in the state. Data used for the study were collected from the forty one registered floricultural plant producers in the study area using structured questionnaire. The farm budget and regression analyses were used for data analyses. The study revealed that returns to farmer’s labour and management was N174, 974.7/ha on the average. Use of manure, labour, farm size, experience, educational level and age of the farmer were found to have significant influence on farmer’s revenue. Inadequate capital to expand the scale of production was identified as the major constraints to floricultural plant production in the study area. The study therefore recommends that farmers be supported by making credit facilities available to them and that people be enlightened on the profitability potential of the enterprise.